Unit selection and HMM-based speech synthesis for Filipino - Lazaro, Lito Rodel S. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
Several speech synthesis systems that are used in many applications such as screen readers and language-learning tools are commercially available in various languages but none are available for Filipino. In this research, two implementations of speech synthesis for Filipino were investigated. The first implementation is an optimization of unit selection using appropriate cost functions and by increasing the amount of speech units in the database to minimize the audible spectral discontinuities in the output. The second implementation, an HMM-based speech synthesis system (HTS), uses statistical parameters and acoustic models instead of actual speech units in generating synthesized speech, which require less memory during runtime. In a listening test that was patterned after the Blizzard Challenge, unit selection synthesis reached an MOS (mean opinion score) of 3.27 fir intelligibility and 2.67 for naturalness. Low scores in naturalness was due to unavailability of necessary samples for unit selection synthesis and the buzzy sound in the output for HTS. We conclude that unit selection synthesis performs better than HTS but would require more speech data to ensure naturalness in the output.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Speech synthesis; Hidden Markov models; Text-to-speech software; Filipino speech synthesizer; HMM-based speech synthesis